64.9k views
2 votes
Help please! and show the steps​

Help please! and show the steps​-example-1
User Romanz
by
4.6k points

1 Answer

4 votes

Answer:

x = 3

x = 2

x= ± √ -1

Explanation:

((((x^4)-(5•(x^3)))+7x^2)-5x)+6 = 0

((((x^4) - 5x^3) + 7x^2) - 5x) + 6 = 0

Dividing : x^4-5x^3+7x^2-5x+6

("Dividend")

By : x-3 ("Divisor")

Quotient : x^3-2x^2+x-2 Remainder: 0

Dividing : x^3-2x^2+x-2

("Dividend")

By : x-2 ("Divisor")

Quotient : x^2+1 Remainder: 0

(x^2 + 1) • (x - 2) • (x - 3) = 0

x^2+1 = 0

x^2 = -1

x = ± √ -1

x-2 = 0

x = 2

x-3 = 0

x = 3

User Plugwash
by
4.9k points